Neuropathological correlates of amyloid PET imaging in Down syndrome - Abrahamson, Eric E.; Head, Elizabeth; Lott, Ira T.; Handen, Benjamin L.; Mufson, Elliott J.; Christian, Bradley T.; Klunk, William E.; Ikonomovic, Milos D. (Developmental neurobiology (Hoboken, N.J.), 2019)
Down syndrome (DS) results in an overproduction of amyloid‐β (Aβ) peptide associated with early onset of Alzheimer's disease (AD). DS cases have Aβ deposits detectable histologically as young as 12–30 years of age, primarily in the form of diffuse plaques, the type of early amyloid pathology also seen at pre‐clinical (i.e., pathological aging) and prodromal stages of sporadic late onset AD. In DS subjects aged >40 years, levels of cortical Aβ deposition are similar to those observed in late onset AD and in addition to diffuse plaques involve cored plaques associated with dystrophic neurites (neuritic plaques), which are of neuropathological diagnostic significance in AD. The purpose of this review is to summarize and discuss findings from amyloid PET imaging studies of DS in reference to postmortem amyloid‐based neuropathology. PET neuroimaging applied to subjects with DS has the potential to (a) track the natural progression of brain pathology, including the earliest stages of amyloid accumulation, and (b) determine whether amyloid PET biomarkers predict the onset of dementia. In addition, the question that is still incompletely understood and relevant to both applications is the ability of amyloid PET to detect Aβ deposits in their earliest form.